2020
DOI: 10.1103/physrevlett.125.245302
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Induced Phonon Dispersion in a Noncentrosymmetric Micropolar Crystal

Abstract: Features of the phonon spectrum of a chiral crystal are examined within the micropolar elasticity theory. This formalism accounts for not only translational micromotions of a medium but also rotational ones. It is found that there appears the phonon band splitting depending on the left-and right-circular polarization in a purely phonon sector without invoking any outside subsystem. The phonon spectrum reveals parity breaking while preserving time-reversal symmetry, i.e., it possesses true chirality. We find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“… ( A ) 3D microstructure unit cell of a metamaterial beam ( 26 ) supporting transverse-like rotons for elastic wave propagation along the z -direction. The blue and red cylinders are responsible for the nearest-neighbor interactions and third-nearest-neighbor interactions, respectively, between the yellow masses.…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) 3D microstructure unit cell of a metamaterial beam ( 26 ) supporting transverse-like rotons for elastic wave propagation along the z -direction. The blue and red cylinders are responsible for the nearest-neighbor interactions and third-nearest-neighbor interactions, respectively, between the yellow masses.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, neither of them captures roton-like behavior. In sharp contrast, it has recently been shown that chiral Eringen micropolar continuum elasticity theory 24 can lead to roton-like dispersion relations for transverse acoustical elastic waves 25 . In their work 25 , chirality has been a necessary mechanism, whereas mechanisms based on periodicity, such as ordinary or extraordinary Bragg reflections, are not accounted for in micropolar elasticity theory 24 .…”
Section: Introductionmentioning
confidence: 96%
“…In sharp contrast, it has recently been shown that chiral Eringen micropolar continuum elasticity theory 24 can lead to roton-like dispersion relations for transverse acoustical elastic waves 25 . In their work 25 , chirality has been a necessary mechanism, whereas mechanisms based on periodicity, such as ordinary or extraordinary Bragg reflections, are not accounted for in micropolar elasticity theory 24 . More broadly speaking, mechanisms such as ordinary Bragg reflection 26 , 27 , local resonances 28 31 , near-ideal joints 32 34 introducing soft modes, spatial or temporal symmetry breaking 35 – 38 , topology 39 , 40 , duality 41 , 42 , as well as geometrical nonlinearities 34 , 43 have independently given rise to a wealth of other unusual dispersion relations and quasi-static behaviors of elastic and acoustical metamaterials.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, it has been theoretically reported that the roton-like dispersion relations for transverse acoustical elastic waves can be realized in noncentrosymmetric micropolar crystal based on chiral micropolar elasticity theory, where chirality is a necessary condition for roton-like behaviours 30 . Hence, it is natural to ask whether chirality plays an important role in the roton-like behaviours in our airborne acoustic system.…”
Section: Roton-like Dispersion Relation In a Chiral Acoustic Metamaterialsmentioning
confidence: 99%